Na cóż to mnichom?” – uwagi na temat cysterskiego podejścia do przedstawień figuralnych .......... 267 - Utzig, Joanna (Dzieje i kultura Cystersów w Polsce, 2025)
‘WHAT GOOD ARE SUCH THINGS TO MONKS?’ – REMARKS ON THE CISTERCIAN ATTITUDE TOWARDS FIGURAL REPRESENTATIONS The Cistercians banned all figural art and excessive decorations in their abbeys. Therefore their attitude towards images and decoration is perceived as aniconic, or even iconoclastic. The famous Apologia ad Guillelmum by St Bernard of Clairvaux is the most iconic text expressing Cistercian criticism of sacred images that, according to the author, are good to common believers, not to educated monks, as they can distract them from their religious practice and involve great inappropriate expense. This skepticism was preceded by other church writings, such as Libri Carolini, claiming that sacred images should not be worshipped. However, St Bernard’s position is different from both the Byzantine iconoclasts – aggressive towards all images – and Western theologians; showing a certain indifference to figural representations, and at least insensitive to their emotional and cult potential. The attitude towards the images and decorations of churches presented by him in the Apology has no direct precedents. An interesting case is the Cistercian approach to representations of the cross. The general chapter of the order forbade them in stained glass, but a single painted cross in a church was acceptable. The unique status of the cross in the Cistercian iconosphere can be associated with the controversy around sacred art in the first millennium, both in Western Europe and in Byzantium, as well as with the later Protestant iconoclasm. Many Cistercian aesthetic ideas reflect their interest in early Christian and early medieval spirituality. This shows their striving to imitate the first Benedictines, whose direct heirs they wanted to pass.